(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
Mathematics is called the queen of science. So the math is the key of the other knowledges learned in school . Mathematics is also considered to be difficult for some students who study mathematics compared to other subjects. This is caused by several factors, including the student’s ability to communicate what is known in the matter is still low. One alternative learning can improve mathematical communication strategy is Active Learning through Group - to- Group. The method used in this study was the experimental method. The study population was all students in class X, while the sample class X - 7 and X - 9 SMAN 22 Bandung. The instrument used in this study was a test and attitude scale. Based on the analysis of research data, it is concluded that: (1) Increasing the mathematical communication abilities of students who get learning strategies Active Learning through Group-to-group better than students who received conventional learning. (2) students’ attitude toward learning math, learning math by using the strategy of Active Learning through Group-to-group, and the mathematical communication are generally positive. This learning can be used as an alternative for teachers in implementing learning activities to address the problems of mathematical communication skills of students. Matematika disebut sebagai ratunya ilmu. Jadi matematika merupakan kunci utama dari pengetahuan-pengetahuan lain yang dipelajari di sekolah. Matematika juga dianggap sukar bagi sebagian siswa yang mempelajari matematika dibandingkan dengan mata pelajaran lainnya. Hal ini disebabkan oleh beberapa faktor diantaranya kemampuan siswa untuk mengkomunikasikan apa yang diketahui dalam soal juga masih rendah. Salah satu alternatif pembelajaran yang dapat meningkatkan komunikasi matematis adalah strategi Active Learning melalui teknik Group-to-Group. Metode yang dipakai dalam penelitian ini adalah metode eksperimen. Populasi penelitian ini adalah seluruh siswa kelas X SMAN 22 Bandung sedangkan sampelnya siswa kelas X-7 dan X-9 SMAN 22 Bandung. Instrumen yang digunakan dalam penelitian ini adalah tes dan skala sikap. Berdasarkan analisis data hasil penelitian, diperoleh kesimpulan bahwa: (1) Peningkatan kemampuan komunikasi matematis siswa yang mendapatkan pembelajaran strategi Active Learning melalui teknik Group-to-Group lebih baik daripada siswa yang mendapatkan pembelajaran konvensional. (2) Sikap siswa terhadap pelajaran matematika, pembelajaran matematika dengan menggunakan strategi Active Learning melalui teknik Group-to-Group, dan terhadap komunikasi matematis yang diberikan pada umumnya bersikap positif. Pembelajaran ini dapat dijadikan sebagai salah satu alternatif bagi guru dalam melaksanakan kegiatan pembelajaran untuk mengatasi permasalahan kemampuan komunikasi matematis siswa.